ANALYSIS OF MODIFIABLE FACTORS ASSOCIATED WITH VENTILATOR-ASSOCIATED PNEUMONIA IN MECHANICALLY VENTILATED PATIENTS IN ICU - Puspitasari, Nabiila; Darmareja, Rycco (Poltekkes Kemenkes Jakarta III, 2025)
Ventilator-associated pneumonia (VAP) is reported as one of the highest nosocomial infection conditions in several countries. Risk factors can be classified into modifiable and non-modifiable factor. This study aims to analyze modifiable factors related to the incidence of VAP in patients using mechanical ventilation. This study used a prospective cohort observational analytic design with a quantitative involving 40 patients with mechanical ventilation in the ICU and selected using purposive sampling. Observation sheets and Clinical Pulmonary Infection Score (CPIS) were used as data collection tools. Hypothesis testing in this study utilized Somers’s d, contingency coefficient, and Kendall’s tau. The analysis revealed significant associations between the duration of mechanical ventilation (p=0.009), and level of consciousness (p=0.021) with the incidence of VAP. However, no significant associations were found between antibiotic use (p=0.075), ICU length of stay (p=0.135), and reintubation (p=0.253) with the incidence of VAP. The study showed that the length of time mechanical ventilation was used and the patient's level of consciousness were factors associated with the incidence of VAP in the ICU. Thus, special attention to modifiable factors can be one of the effective strategies in reducing the incidence of VAP in the ICU.